A META SYNTHESIS: ISLAMIC EDUCATION OF COVID PSYCHOTHERAPHY - Siti Seituni; Nurzannah Nurzannah; Hajar Nurma Wachidah; Refika Refika; Dian Cita Sari (Proceeding International Seminar of Islamic Studies, 2022)
There have conclusions are vital for the building of paradigm of Islamic Education of Covid Psychotheraphy science that was work with Dutch East Indies Covid. This study tried to synthesis qualitative analysis of Islamic education of Covid Psychotherapy to explain real expertise. Technique of this analysis was qualitative meta synthesis. The approach utilized in this analysis was reciprocal translation, that tailored from meta anthropology. From the result, Islamic education of covid psychotheraphy was outlined as Techniques to unravel the clients issues and treating unhealthiness each mental, spiritual, moral, or physical by increasing the attention of God and obtaining back the shopper to God, in Islam Covid approach through steerage of sacred text and hadits. Its 3 varians of Islamic education of covid psychotheraphy: religious mysticism, worship psychotherapy, and spiritual steerage. Supposition regarding fitrah and tauhid found underlying all the concepts and follow of Islamic education of covid psychotheraphy in Dutch East Indies. Keywords: Islamic Education, Covid psychotherapy, meta synthesis, qualitative